Antiparkinsonian activity of selective MAO-B inhibitors of different chemical structures - Vladimir N. Fedorov; Mikhail K. Korsakov; Anton A. Shetnev; Sergey S. Petukhov; Nikita N. Volkhin; Vladimir P. Vdovichenko; Anastasia A. Khokhlova; Salavat Sh. Suleymanov (Research Results in Pharmacology)
Introduction: Parkinson’s disease (PD) is a chronic neurodegenerative disease of the central nervous system, the pathogenesis of which is associated with the death of dopaminergic neurons of the midbrain substantia nigra. The mainstay of therapy for PD is levodopa. However, in the initial stages of PD or in case of levodopa intolerance, MAO B inhibitors are used. Purpose of the study was to determine antiparkinsonian activity of newly synthesized selective MAO-B inhibitors in vivo on the model of experimental parkinsonism in white mice.